Greenhouse gas emissions from broiler manure treatment options are lowest in well-managed biogas production. (20th January 2021) - Kreidenweis, Ulrich; Breier, Jannes; Herrmann, Christiane; Libra, Judy; Prochnow, Annette
Abstract: The production of broiler meat has increased significantly in the last decades in Germany and worldwide, and is projected to increase further in the future. As the number of animals raised increases, so too does the amount of manure produced. The identification of manure treatment options that cause low greenhouse gas emissions becomes ever more important. This study compares four treatment options for broiler manure followed by field spreading: storage before distribution, composting, anaerobic digestion in a biogas plant and production of biochar. For these options potential direct and indirect greenhouse gas emissions were assessed for the situation in Germany. Previous analyses have shown that greenhouse gas balances of manure management are often strongly influenced by a small number of processes. Therefore, in this study major processes were represented with several variants and the sensitivity of model results to different management decisions and uncertain parameters was assessed. In doing so, correlations between processes were considered, in which higher emissions earlier on in the process chain reduce emissions later. The results show that biogas production from broiler manure leads to the lowest greenhouse gas emissions in most of the analysed cases, mainly due to the emission savings related to the substitution of mineral fertilizers and the production of electricity. Pyrolysis of the manure and subsequent field spreading as a soil amendment can lead to similarly low emissions due to the long residence time of the biochar, and may even be the better option than poorly managed biogas production. Composting is the treatment option resulting in highest emissions of greenhouse gases, due to high ammonia volatilization, and is likely worse than untreated storage in this respect. These results are relatively insensitive to the length of transport required for field spreading, but high uncertainties are associated with the use of emission factors. Highlights: Comparison of greenhouse gas emissions from manure treatment. Novel approach that considers parameter interdependencies and uncertainties. Biogas production from broiler manure results in lowest emissions. Results strongly influenced by management decisions and emission factors.